Evaluation of a Social Skills Program for Early Elementary Students: We Have Skills. Issue 4 (2nd October 2022) - Smolkowski, Keith; Walker, Hill; Marquez, Brion; Kosty, Derek; Vincent, Claudia; Black, Carey; Cil, Gulcan; Strycker, Lisa A.
Abstract: This paper reports the results of a randomized controlled trial evaluating We Have Skills, a brief curriculum designed to teach early elementary students academic and social skills as well as improve teacher efficacy in classroom management. Intervention efficacy was tested with 127 teachers, randomly assigned to condition, and 2, 817 of their students. On key outcomes of student academically related behavioral skills and classroom adjustment, intervention teachers reported greater gains for their students than comparison teachers (Hedges's g  ≥ 0.19). Baseline scores moderated effects, demonstrating greater differences between conditions for initially struggling students. Intervention teachers also reported greater improvements on their sense of self-efficacy for classroom management and concerns about student behavior (| g | ≥ 0.30) relative to comparison teachers. Effect sizes were similar to or greater than those reported for similar programs, and an economic analysis suggested that We Have Skills was less costly than many. The findings support cost-effective solutions that teach social–behavioral skills in early elementary grades—and suggest that such programs may be especially beneficial for students who struggle with academically related behaviors.